Charged-particle multiplicities in pp interactions at √s=900 GeV measured with the ATLAS detector at the LHC - Aad, Georges; Andrei, George Victor; Dietzsch, Thorsten; Hanke, Paul; Khomich, Andrei; Kluge, Eike-Erik; Kugel, Andreas; Männer, Reinhard; Meier, Karlheinz; Müller, Felix; Poddar, Sahill; Radescu, Voica; et al. (Physics letters, 2010)
The first measurements from proton-proton collisions recorded with the ATLAS detector at the LHC are presented. Data were collected in December 2009 using a minimum-bias trigger during collisions at a centre-of-mass energy of 900 GeV. The charged-particle multiplicity, its dependence on transverse momentum and pseudorapidity, and the relationship between mean transverse momentum and charged-particle multiplicity are measured for events with at least one charged particle in the kinematic range |η|<2.5 and pT>500 MeV. The measurements are compared to Monte Carlo models of proton-proton collisions and to results from other experiments at the same centre-of-mass energy. The charged-particle multiplicity per event and unit of pseudorapidity at η=0 is measured to be 1.333±0.003(stat.)±0.040(syst.), which is 5-15% higher than the Monte Carlo models predict.
*ATLAS Collaboration: G. Aad, V. Andrei, T.A. Dietzsch, P. Hanke, A. Khomich, E.-E. Kluge, A. Kugel, R. Maenner, K. Meier, F. Mueller, S. Poddar, V. Radescu, S. Schaetzel, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und 3206 weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 31.10.2022